Propuesta de automatización de la Gestión documental en el departamento de cultura de la Uleam: Un diagnóstico preliminar - Muñoz, Juan Carlos; Berbey Álvarez, Aranzazu (Proceedings of the LACCEI international Multi-conference for Engineering, Education and Technology, 2020)
The following article corresponds to a proposal of automation of document management in the Department of Culture of the Universidad Laica Eloy Alfaro de Manabí (Ecuador). This article is divided into introduction, context and state of the art, objectives and work methodology, specific development of the contribution, discussion and results, conclusions and future lines of work.
Documentation management automation proposal in the Department of Culture of ULEAM: A preliminary diagnosis
Ponencia de la conferencia "16th LACCEI International Multi-Conference for Engineering, Education Caribbean Conference for Engineering and Technology; Lima; Peru; 18 July 2018 through 20 July 2018"
Keywords: department of culture; documentary management; software; university; Scopus(2)